Discourse Analysis and Digital Humanities: Review of Digital Tools for Data Analysis - Torres Calderón, Gina (2024)
This paper examines the main proposals of discourse analysis and critical discourse analysis, as well as their relationship with the Digital Humanities. In addition, it presents a series of examples of research work carried out at the University of Costa Rica, with the aim of serving as a model for a wider application of Digital Humanities in the classrooms of this institution, mainly those linked to the areas of study in question. It also outlines examples of some of the current qualitative analysis tools with short tutorials for their basic use. Finally, a list of recommendations is presented that will be useful to academic staff who want to approach this multidisciplinary area of knowledge for the first time.